The girl in the ice - Bryndza, Robert (New York : Grand Central, 2018)
When a young boy discovers the body of a woman beneath a thick sheet of ice in a South London park, Detective Erika Foster is called in to lead the murder investigation. The victim, a beautiful young socialite, appears to have had the perfect life. Yet when Erika begins to dig deeper, she starts to connect the dots between the murder and the killings of three prostitutes, all found strangled, hands bound and dumped in water around London. As Erika inches closer to uncovering the truth, the killer closes in on Erika. provided by the publisher
Originally published in 2016 by Bookouture, an imprint of Storyfire.
Includes an excerpt from: The night stalker.
Keywords: Women detectives -- England -- London -- Fiction; Serial murderers -- Fiction; Prostitutes -- Crimes against -- Fiction; Serial murder investigation -- Fiction; London (England) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)